INTEGRASI NILAI-NILAI MULTIKULTURAL DALAM KONTEKS PENDIDIKAN AGAMA ISLAM DI SMPN 13 MALANG - Umam, Rizal Khoirul; Marno, Marno (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Indonesia is a country rich in culture, religion and ethnicity. This diversity gives strength but also poses challenges, especially in maintaining harmony. Multicultural education in Islamic Religious Education lessons has long been discussed, but applying these values is still not optimal. So, it is very important to integrate the values of multicultural education at all levels of education in Indonesia, including at the junior high school level, as a foundation for character building in early adolescence. This research aims to explore more deeply how multicultural values are implemented in SMPN 13 Malang and how multicultural values can be integrated into the context of Islamic Education. This research uses a qualitative approach with the type of case study. The subjects in this research are the vice curriculum, Islamic Education teachers and student representatives. The data were collected through observation, interview, and documentation methods, while the data were analysed with descriptive qualitative through data reduction, data presentation and conclusion drawing. The result of this research shows that SMPN 13 Malang applies multicultural values such as tolerance value, equality value, and freedom value. Meanwhile, multicultural values in Islamic Religious Education learning at SMPN 13 Malang are integrated through various aspects such as the materials, methods, and teaching media.